The current issues of internal control and internal audit harmonization - Синюгіна, Наталія Вікторівна (Technology audit and production reserves, 2013)
The relevance of topics related to a harmonization of internal control and internal audit system of internal financial control is being proved. It is high lightened the essence of harmonization period by reviewing existing thoughts on this object, a concept of ’harmonization of internal control and internal audit", and provided reasonably practical recommendations to ensure such harmonization in the modern world. The scientific impact of this research is to clarify the concept of "harmonization of internal control and internal audit" as well as the development of practical recommendations to ensure proper harmonization of internal control and internal audit in the system of public internal financial control in Ukraine.